Antihypertensive drug-associated adverse events in osteoarthritis: a study of a large real-world sample based on the FAERS database - Guo, Zijian; Di, Jingkai; Zhang, Zhibo; Chen, Shuai; Mao, Xingjia; Wang, Zehua; Yan, Zehui; Li, Xiaoke; Tian, Zui; Mu, Changjiang; Xiang, Changxin; Xiang, Chuan (Frontiers in Pharmacology, 2024)
Background: Hypertension is a common complication in patients with osteoarthritis (OA). There is increasing interest in the relationship between hypertension and OA. However, hypertension has been reported to negatively affect symptoms and quality of life in patients with OA. Therefore, treating hypertension is crucial for patients with OA. However, there is a lack of real-world studies on the effects of medications for treating hypertension on OA. Methods: Data from the FAERS database from January 2004 to December 2023 were extracted for disproportionality analyses, and proportional reporting ratios (PRRs) were used to assess the association between medications for hypertension and all types of arthritis. Adverse event signals were identified and determined using reporting odds ratios (RORs) Adverse event signals were considered to have occurred if a drug-induced adverse event was recorded more than or equal to 3 and the lower limit of the ROR confidence interval was more than 1. We selected five classes of drugs including, calcium channel blockers (CCBs), angiotensin converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), thiazide diuretics and β-blockers and representative drugs were analysed for osteoarthritis-related adverse reactions, and age and gender subgroups were analysed for drugs of significance. We also analysed the occurrence of AEs in relation to time using the Weibull distribution. Results: In terms of overall data, we found significant OA adverse reaction signals only for ARBs among the five drug classes.ARB AEs for spinal osteoarthritis (ROR 4.64, 95% CI 3.62 - 5.94), osteoarthritis (ROR 3.24 95% CI 2.82- 3.72) and gouty arthritis (ROR 3.27 95% CI 1.22- 8.75) were the three adverse reactions with the loudest signals. Next, we found that valsartan had strong osteoarthritis adverse reaction signals among the three ARBs, namely, irbesartan, cloxartan, and valsartan. We also analysed age and gender subgroups and found that osteoarthritis signals were strongest in the 18-65 and 65+ population, while females seem to be more prone to valsartan-related OA AEs. Conclusions: ARBs, especially valsartan, have significant positive signals for OA AEs. Therefore, ARB drugs, especially valsartan, should be used with caution when treating patients with OA combined with hypertension.